Validity and reliability of Perceived Social Support Scale (MSPSS) - Xóchitl Santos-Vega, María; Ortega-Andeane, Patricia; Toledano-Toledano, Filiberto (Psicooncología, 2021)
Introduction: There is evidence that social support is a fundamental variable in research and intervention with families in the context of health and chronic disease. Aims: Obtain evidence of validity and reliability of the Perceived Social Support Scale (MSPSS) in informal primary caregivers of patients with cancer. Methods: Instrumental study, in which a non-probabilistic sample of 257 informal primary caregivers (CPI) who attended outpatient consultation at a National Institute of Health in Mexico City for cancer treatment was interviewed. Participants were mostly woman (88,3%)with ages ranging from 18 to 65 years (M = 31, SD = 9,06); were married (45,6%) and approximately 61.11% had children and spent more than 30 hours a week caring for the patient (61,11%). Caregivers answered a questionnaire of sociodemographic and clinical data, the MSPSS (translated into Spanish) and the Kessler Psychological Discomfort Scale (K-10). Results: Confirmatory factor analysis showed the following fit indices for the MSPSS: CMIN: 55.23; GFI: 0, 997; AGFI: 0,995; NFI: 0,996; RMR: 0,053. Reliability coefficient for the full scale was 0,908. In addition, the validity of divergent criteria was tested by correlating the MSPSS scores and the K-10 scores. Conclusions: This study provides satisfactory validity and reliability evidence for the MSPSS and, therefore, is a useful instrument for measuring social support in populations of family caregivers of patients with chronic diseases.
Keywords: Social support; validity; reliability; primary caregivers; cancer